Mechanochemical remediation of fluoranthene contaminated soil and biotoxicity evaluation - Yao, Zhenzhen (Environmental technology, 2023)
A mechanochemical (MC) method was employed for the remediation of soil contaminated with fluoranthene (C16H10, FL) a four-ringed polycyclic aromatic hydrocarbon (PAH) containing three benzene rings and a central five-membered heterocyclic ring, with the effects of soil inorganic components, milling conditions, and the degradation mechanism investigated. Results showed that the addition of SiO2 and kaolin to soil resulted in a greater increase in the effectiveness of FL removal than other inorganic additives. After 3 hours of milling at 500 rpm, the FL removal rate from SiO2 containing soil, reached 99.26%, with the removal efficiency increasing in accordance with an increase in milling duration and speed. The milled samples were characterized by FT-IR, Raman spectroscopy, and GC-MS analysis, revealing the mechanism of FL degradation, including destruction of the aromatic skeleton structure and the formation of amorphous carbon and graphite. The MC remediation method was applied to FL contaminated soil, showing that FL was efficiently degraded in soil without any soil additives, resulting in a significant reduction in the biotoxicity of the remediated soil. The organic matter, moisture content and pH of the actual soil changed slightly after mechanical ball milling. Thus, the MC method has high potential in the remediation of PAH-contaminated soils.HIGHLIGHTSA mechanochemical (MC) method for the degradation of fluoranthene was assessed.The use of silica and kaolin as soil additives enhances fluoranthene remediation.Fluoranthene can be efficiently removed from contaminated soil by milling alone.The degradation mechanism was skeleton structure destruction and carbonization.The biotoxicity of soil was significantly reduced by milling